Medical factors associated with caregiver intention to vaccinate their children against COVID-19. (April 2022) - Phan, Thao-Ly T.; Enlow, Paul T.; Wong, Michael K.; Lewis, Amanda M.; Kazak, Anne E.; Miller, Jonathan M.
Highlights: We link caregiver-reported data to child EHR data to understand COVID-19 vaccine hesitancy. Caregiver COVID-19 vaccine hesitancy was associated with child influenza immunization history. Caregiver COVID-19 vaccine hesitancy was not associated with other child immunization history. Caregiver COVID-19 immunization was associated with vaccine hesitancy for their child. Child disease risk factors were not associated with caregiver COVID-19 vaccine hesitancy. Abstract: Objective: To describe medical factors that are associated with caregiver intention to vaccinate their children against COVID-19. Methods: We conducted a cross-sectional study of families receiving primary care in a mid-Atlantic pediatric healthcare system, linking caregiver-reported data from a survey completed March 19 to April 16, 2021 to comprehensive data from the child's EHR. Results: 513 families were included (28% Black, 16% Hispanic, 44% public insurance, 21% rural, child age range 0–21 years). 44% of caregivers intended to vaccinate their children against COVID-19, while 41% were not sure and 15% would not. After adjusting for socio-demographics, the only medical factors that were associated with caregiver COVID-19 vaccine hesitancy were caregiver COVID-19 vaccination status at the time of the survey (aOR 3.0 if the caregiver did not receive the vaccine compared to those who did, 95% CI 1.7–5.3) and child seasonal influenza immunization history (aOR 3.3 if the child had not received the influenza vaccine in the 2020–2021 season compared to those who did, 95% CI 2.0–5.4). Other medical factors, including family medical experiences with COVID-19, other child immunization history, child health conditions like obesity and asthma, and family engagement with the healthcare system were not associated with caregiver intention to vaccinate their children against COVID-19. Conclusions: This study highlights important factors, such as general attitudes towards vaccines and understanding of COVID-19 morbidity risk factors, that healthcare providers should address when having conversations with families about the COVID-19 vaccine.